2020
DOI: 10.21705/mcbs.v4i2.90
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antiaging and Antioxidant Activities of Protocatechuic and Ferulic Acids

Abstract: Background: Skin-aging is a progressive changes in the skin combine with cumulative extrinsic factors which are mostly caused by free radicals caused by exposure to lots of free radicals molecules from pollutant, wrongly food intake, or too much sun bathing. These free radicals can be tackled by a treatment using antioxidants. Prevention of aging can be done by escalating antioxidant intake. Protocatechuic acid (PCA) and Ferulic acid (FA) have been known for their scavenging properties on free radicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[ 1 , 2 ]. FA is known as an antiaging [ 3 ], anti-inflammatory [ 4 ], antithrombotic [ 5 ], antidiabetic [ 6 ], antiulcerigen [ 7 ], antihemolitic [ 8 ], antiviral [ 9 ] and even anti-carcinogenic agent [ 10 ]. Due to the antibacterial effect, it may also be used in certain implants [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ]. FA is known as an antiaging [ 3 ], anti-inflammatory [ 4 ], antithrombotic [ 5 ], antidiabetic [ 6 ], antiulcerigen [ 7 ], antihemolitic [ 8 ], antiviral [ 9 ] and even anti-carcinogenic agent [ 10 ]. Due to the antibacterial effect, it may also be used in certain implants [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that gallic acid coated with gold nanoparticles has a superior ability to inhibit the degradation of type I collagen mediated by high glucose in dermal fibroblast cells (Wu et al, 2021). Another study illustrated that the collagenase inhibition activity of ferulic acid is 52.85 µg/mL, which falls into the strong category (Girsang et al, 2020). With collagenase inhibition activity and DPPH scavenging, SBPE shows promising potential as a good antioxidant and anti-aging agent.…”
Section: Discussionmentioning
confidence: 97%
“…Kojic acid was used as the positive control. The collagenase and tyrosinase inhibitory activity was calculated using the following equation [31]:…”
Section: Anti-aging Activity Assaymentioning
confidence: 99%
“…Compounds with antioxidant activity could prevent aging by inhibiting the activities of ROS and aging enzymes [31]. The ROS activates the MAPK pathway, which increases microphthalmia-associated transcription factor (MITF) expression and thus tyrosinase-regulated melanogenesis [5].…”
Section: Anti-aging Activitymentioning
confidence: 99%